Unions of Catholic Journeymen. Contribution to the History of Czech Christian-Social Movement Formation - Marek, Pavel (Historica Olomucensia, 2011)
The aim of this contribution is the search for the position of Catholic journeymen unions as the first associations of young workers and craftsmen in the Czech Lands in the prehistory of the Christian-social movement. The study refers to the causes of the journeymen movement formation in the Czech Lands which was adopted from the German area. It expounds its activity through a case study about the history of the union in Prague. In the second part of the article the author mentions some facts about the life and work of P. František Koželuha, one of the protagonists of this movement in the Czech area, on the background of his activity in Prostějov. The final part of this essay deals with the causes of the journeymen movement decline starting at the beginning of the 20th century. The conclusion is drawn that the movement was replaced by activities of Catholic political associations and political parties which created affiliated organizations. These organizations contributed to the solution of social problems in the form of self-help which replaced or supplemented the charity. The article presents some insight from the point of view of Czech political Catholicism genesis which enriched the party-political system of the Czech Lands with political parties based on denominational principles.